Longterm biomechanical performance diagnostics with the german national gymnastics team - Nissinen, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Scientific research in gymnastics has become a vital part of high level coaching. The systematic biomechanical performance diagnostics with the German national gymnastics team started in 1978. Several investigations were conducted in training and competitive situations. After the foundation of the Olympic Training Centre in Frankfurt (1986) greater emphasis has been placed on direct application of reseach results. A new comprehensive project for the 2008 Olympic Games will be conducted by German Sport University.